PEMANFAATAN LIMBAH SHAVING DAN BUFFING KULIT SAMAK KROM SEBAGAI BAHAN BAKU GANTUNGAN KUNCI MENGGUNAKAN PEREKAT POLIURETAN - Himawan Santoso; Wahyu Fajar Winata (Politek ATK Yogyakarta Press, 2026)
The leather tanning industry generates solid waste, such as shaving and buffing waste, which may cause environmental problems if not properly utilized. One approach to increasing the value of this waste is to convert it into handicraft products with economic value. This study aimed to utilize chrome-tanned leather shaving and buffing waste as raw materials for keychain production using polyurethane adhesive through the pulp slurry method. Shaving and buffing waste were mixed at a ratio of 1:1, followed by the addition of polyurethane adhesive and Fox Glue in two formulations (1:3 and 3:1). The mixture was processed into a pulp slurry, molded, dried, and subsequently subjected to a plating process at 80°C for 1.5 seconds under a pressure of 3 MPa before being engraved into keychain products. The results demonstrated that the leather waste could be formed into compact sheets with a smoother surface after the plating process. The resulting material was successfully applied as a keychain, thereby adding value to leather tanning waste. The developed product also has the potential to support ergonomic product design through its lightweight characteristics, ease of handling, and efficient manufacturing process, although ergonomic performance was not directly evaluated in this study. The utilization of shaving and buffing waste has the potential to support the implementation of cleaner production and circular economy principles by reducing solid waste generation while creating value-added products.